University Students' Experiences During COVID-19: Insights from Online/Distance Education - Rabia Kıvanç; Çiğdem Aytekin (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: The COVID-19 pandemic caused unprecedented disruptions in higher education, compelling a rapid transition to distance learning and altering students’ academic and psychosocial functioning. This study aimed to examine perceived stress levels among university students enrolled in Child Development departments and to identify the educational deprivations they experienced during pandemic-related remote instruction. Materials and Methods: A convergent mixed-methods design was employed. Data were collected from 161 undergraduate students using a Demographic Information Form, The Deprivations in Distance Education Form, and the Perceived Stress Scale. Quantitative data were analyzed using appropriate parametric and non-parametric statistical procedures, and effect sizes were reported. Qualitative data obtained from open-ended responses were analyzed using descriptive content analysis. Findings from both strands were integrated through a joint display. Results: Perceived stress levels differed significantly according to university type, place of residence, personal computer ownership, and household job loss. Higher stress was also associated with inadequate access to a quiet study space, difficulties attending online classes, communication barriers with instructors, and challenges in receiving academic feedback. Qualitative findings revealed prominent technological, environmental, economic, and professional practice-related deprivations that aligned with statistically significant differences in stress. Conclusion: The findings suggest that perceived stress during distance education was closely associated with structural and contextual educational constraints. Strengthening technological infrastructure, improving instructional communication, and ensuring equitable access to digital resources may help mitigate stress experiences in remote learning contexts. Beyond the pandemic, the results underscore the importance of designing resilient, inclusive online and hybrid learning environments in higher education.